A tale of time city - Jones, Diana Wynne (New York : Firebird, 2012)
"London, 1939. Vivian Smith thinks she is being evacuated to the countryside because of the war. But she is being kidnapped--out of her own time. Her kidnappers are Jonathan and Sam, two boys her own age, from a place called Time City. Built eons ago on a patch of space outside time, Time City was designed especially to oversee history. But now history is going critical, and Jonathan and Sam are convinced that Time City's impending doom can only be averted by a Twenty Century girl named Vivian Smith. Too bad they have the wrong girl ..."--Cover
Keywords: Time travel -- Fiction; Science fiction